The Publish or Perish Doctrine and Declining Commitment to Writing - Md. Mahmudul Hasan (Asiatic: IIUM Journal of English Language and Literature, 2026)
Writers usually write in response to an intrinsic calling to express themselves, instruct the public, or enlighten the reader. Their urge for documenting their ideas and experiences comes from within, as they take the writing career as an expression of the self and as a vehicle of thought and human progress. Given the development of the modern education system, academics of tertiary institutions are found to write even if they do not possess such a bent of mind or innate artistic talent. As a result, there has been a sharp increase in the number of writers and writings. However, when academics write without passion or inspiration, they exhibit certain authorship traits and publication behaviours which are not helpful for editors. Based on my editorial experience, I shall comment on certain authors’ lack of passion for scholarship or for their work, making a case for active authorial involvement from the conception of a manuscript to its publication.